Impact of uncertainties associated with the choice of the yield stress on the prediction of subsurface reservoir compaction: A field study - Amour, Frédéric; Hajiabadi, Mohammad Reza; Nick, Hamidreza M. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2023)
The compaction of subsurface chalk during hydrocarbon production leads to technical and societal issues related to well trajectory design, wellbore collapse, seafloor subsidence, and seismic events. Predicting reservoir deformation over time requires well-calibrated constitutive equations to capture the viscoplastic response of chalk according to several parameters including porosity, age, water saturation, and rate of applied stress or strain. The experimental data used to extrapolate trends between e.g., porosity and yield stress, show a non-negligible data scattering, thereby raising questions about the reliability of the predicted compaction. The present study aims at assessing how the uncertainty associated with the determination of the yield stress manifests itself at the field scale. To this purpose, one-dimensional simulations are performed on four producing hydrocarbon reservoirs from the Danish North Sea and quality-checked against seafloor subsidence measurements. Two simulations are run per case study by considering in the constitutive equations the initial (conservative approach) and final (optimistic approach) yield stress values, which delimit the transition between the elastic and plastic regime of chalk. The results indicate that the accumulated strain and the seafloor subsidence vary by a factor of up to 73% and 50%, respectively between the conservative and optimistic approaches. These differences in the compaction behaviour are influenced by three parameters, the initial porosity, the virgin stress condition, and the stress history of the reservoir. This study demonstrates that the uncertainty analysis of compaction simulation studies is essential for estimation of compaction drive of hydrocarbon fields and to identify the locations potentially subject to failure in the context of hydrocarbon production and field abandonment as well as CO2 and thermal storage projects. •Quantifying uncertainties related to the prediction of reservoir compaction.•The method for estimating the yield stress impacts simulation outcome.•Yield stress values tested are representative of reservoir chalk from the North Sea.•The models are tested against field data and validated by seafloor subsidence data.•Initial porosity and in situ stress impact discrepancy between compaction scenarios.